Assesing The Performance of Construction Workers in Peninsula Malaysia - Zolkafli, U.K.; Hanid, M.; Zakaria, N. (2009)
Manpower is the most valuable asset in the construction industry. Workers’ performance is an important factor contributing to the timely completion and success of a construction project. The construction industry in Malaysia is labour intensive. Unfortunately, most empirical studies have revealed that the output of the industry is quite low when compared with many developed countries. This paper assesses the performance of construction workers in Peninsula Malaysia and finds some useful measures which would contribute towards its improvement.